Halal food facilities in Japan from the perspective of Malaysian muslim tourists - Wan Sulong, Wan Muhammad; Husain, Salina; Ismail, Muhd Zulkifli; Othman, Mohd Sukki; Mohd Zin, Zaid; Mohd Ghazali, Rabihah (Human Resource Management Academic Research Society, 2020)
In addition to being a popular destination for tourists worldwide, Japan is getting high marks for its efforts to become a halal-friendly tourist destination. Halal or Islamic tourism is a market segment that is fast growing not only in Muslim countries but globally due to the rapid growth of the Muslim population. Japan is at the top of the list of countries that increase their hospitality to Muslim customers. The purpose of this study is to investigate the perspective of Malaysian Muslims tourists towards halal food facilities based on their experience of a visit to Japan. Surveys via the questionnaire are the method used for data collection. The outcome of the study shows that respondents are very concerned about the halal status of food due to their understanding of the concept of halal food. Therefore, most of them only choose food that is believed to be permitted especially those with halal logo. Halal food is relatively easy to get at the airport and major tourist attractions. The presence of Muslim workers in halal premises adds to their confidence in the halal food provided. In terms of cost, respondents are less satisfied because the cost of halal food is relatively expensive.